Inhibition of nuclear transport of NF-kB p65 by the Salmonella type III secretion system effector SpvD - Rolhion,N; Furniss,R; Grabe,G; Ryan,A; Liu,M; Matthews,S; Holden,DW (Plos Pathogens, 2016)
Salmonella enterica replicates in macrophages through the action of effector proteins translocated across the vacuolar membrane by a type III secretion system (T3SS). Here we show that the SPI-2 T3SS effector SpvD suppresses proinflammatory immune responses. SpvD prevented activation of an NF-B-dependent promoter and caused nuclear accumulation of importin-α, which is required for nuclear import of p65. SpvD interacted specifically with the exportin Xpo2, which mediates nuclear-cytoplasmic recycling of importins. We propose that interaction between SpvD and Xpo2 disrupts the normal recycling of importin-α from the nucleus, leading to a defect in nuclear translocation of p65 and inhibition of activation of NF-B regulated promoters. SpvD down-regulated pro-inflammatory responses and contributed to systemic growth of bacteria in mice. This work shows that a bacterial pathogen can manipulate host cell immune responses by interfering with the nuclear transport machinery.